Kultura codzienności jako czynnik kształtujący orientacje życiowe = Everyday culture as a factor in developing life expectations - Ferenz, Krystyna (Zielona Góra: Uniwersytet Zielonogórski)
Personality does not materialize outside the framework of a social group, whose values demarcate the limits of one's own social identity. This condition may well be accepted, but may also be fought against in order to elicit changes. The resulting life expectations will be closely dependent on the level of self-acceptance displayed by an individual, which in tum will have been strongly influenced by his everyday surroundings. The self-image is not necessarily constant and may undergo certain fluctuations due to educational influence, which contributes to his liberation from the stereotypes and prejudices acquired at the earlier stages of life.
Keywords: kultura; człowiek; społeczeństwo